Critical assessment of thermodynamic properties of important polycyclic aromatic hydrocarbon compounds (PAHs) in coal tar pitch at typical temperature ranges of the carbonization process. (September 2021) - Hosseini, Mahnaz Soltani; Chartrand, Patrice
Abstract: Because of the importance of thermodynamic behavior of Polycyclic Aromatic Hydrocarbon (PAH) compounds in coal tar pitch carbonization process, a thermodynamic model for the prediction of thermodynamic properties of PAH compounds is developed. Heat capacity functions as well as standard thermodynamic properties of PAHs in solid, liquid, and gas states are estimated using modified group additivity algorithms first proposed by Richard and Helgeson and thermal physical data of those PAHs for which enough experimental data exists in the literature. For the first time, initial calculated thermodynamic properties of PAHs are optimized by applying the CALPHAD (CaLculation of PHAse Diagrams) approach where all thermodynamic data are rendered consistent with phase transitions and vapor pressure data. The heat capacity function of PAHs exhibiting thermal anomaly behavior is modeled as a specific case. This modeling is performed using an order-disorder approach with the Compound Energy Formalism (CEF). Good agreement has been obtained between the predicted thermodynamic properties of PAHs and available experimental data. The proposed model has improved the predictive capacity compared to that of the previous models predicting thermodynamic properties of PAHs at typical temperature ranges of the carbonization process. The application of the model to predict the thermodynamic properties of major and high molecular weight PAHs available in coal tar pitch has been discussed.